A molecular understanding of the catalytic cycle of the nucleotide-binding domain of the ABC transporter HlyB. (26th October 2005) - Zaitseva, J.; Jenewein, S.; Oswald, C.; Jumpertz, T.; Holland, I.B.; Schmitt, L.
Abstract : The ABC transporter (ATP-binding-cassette transporter) HlyB (haemolysin B) is the central element of a type I secretion machinery, dedicated to the secretion of the toxin HlyA in Escherichia coli . In addition to the ABC transporter, two other indispensable elements are necessary for the secretion of the toxin across two membranes in a single step: the transenvelope protein HlyD and the outer membrane protein TolC. Despite the fact that the hydrolysis of ATP by HlyB fuels secretion of HlyA, the essential features of the underlying transport mechanism remain an enigma. Similar to all other ABC transporters, ranging from bacteria to man, HlyB is composed of two NBDs (nucleotide-binding domains) and two transmembrane domains. Here we summarize our detailed biochemical, biophysical and structural studies aimed at an understanding of the molecular principles of how ATP-hydrolysis is coupled to energy transduction, including the conformational changes occurring during the catalytic cycle, leading to substrate transport. We have obtained individual crystal structures for each single ground state of the catalytic cycle. From these and other biochemical and mutational studies, we shall provide a detailed molecular picture of the steps governing intramolecular communication and the utilization of chemical energy, due to ATP hydrolysis, in relation to resulting structural changes within the NBD. These data will be summarized in a general model to explain how these molecular machines achieve translocation of molecules across biological membranes.